Electrical discharge machining of the AISI D6 tool steel: Prediction and modeling of the material removal rate and tool wear ratio - Barenji, Reza Vatankhah; Pourasl, Hamed H.; Khojastehnezhad, Vahid M. (Elsevier Science Inc, 2016)
In this investigation, response surface method was used to predict and optimize the material removal rate and tool wear ratio during electrical discharge machining of AISI D6 tool steel. Pulse on time, pulse current, and voltage were considered as input process parameters. Furthermore, the analysis of variance was employed for checking the developed model results. The results revealed that higher values of pulse on time resulted in higher values of material removal rate and lower amounts of tool wear ratio. In addition, increasing the pulse current caused to higher amounts of both material removal rate and tool wear ratio. Moreover, the higher the input voltage, the lower the both material removal rate and tool wear ratio. The optimal condition to obtain a maximum of material removal rate and a minimum of tool wear rate was 40 mu s, 14 A and 150 V, respectively for the pulse on time, pulse current and input voltage. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Electrical discharge machining; AISI D6 tool steel; Response surface method